Financial statements vs. FinTech: A discussion of Minnis, Sutherland, and Vetter - Demerjian, Peter (Journal of Accounting and Economics, 2024)
Minnis, Sutherland, and Vetter (MSV) documents a sharp decline in lenders’ collection of attested financial statements (including unqualified audits, reviews, and compilations) over the period 2002 to 2017. They attribute this change to lenders adopting new technology and new non-bank lenders entering the lending market. In this discussion, I explore several dimensions of their findings. First, I provide a framework for usefulness of financial statement information in debt contracting. Using this framework, I consider how financial statements may be useful for the small and medium loans the authors study, and how this role could be disrupted. Second, I consider how financial technology (FinTech) has disrupted traditional lending and potentially changed the role of financial statements. Finally, I consider the implications for this change on the accounting profession.